The CellFlux Storage Concept for Increased Flexibility in Sensible Heat Storage. (June 2015) - Odenthal, Christian; Steinmann, Wolf-Dieter; Eck, Markus
Abstract: Packed beds using air at atmospheric pressure as heat transferringmedium are the most cost effective systems for sensible heat storage. The basic idea of the CellFlux concept is to apply this concept also for liquid and/or pressurized primary HTFs by the introduction of an intermediate working fluid cycle. A heat exchanger is used for transferring energy between the primary HTF and the intermediate air cycle which eventually transfers the energy to a packed bed. The CellFlux concept can be implemented by using standard components. Essential is the minimization of efficiency losses resulting from the circulation of the air as well as the heat transfer processes within the heat exchanger and the storage volume. Some example cost estimations for the heat exchanger are given. The feasibility of the CellFlux concept has been proven by a pilot scale test facility operated at a maximum temperature of 380 °C and 100 kW. A novel approach promising further cost reductions has been applied by realizing a horizontal flow direction. Results from the theoretical and experimental analysis of the CellFlux concept will be presented. Distinctive for the CellFlux concept is the flexibility regarding working fluid (thermal oil, molten salt, pressurized water, CO2 ), temperature range (0-800 °C), power (kW-multi MW) and storage medium (rocks, clinker bricks, concrete). This allows a wide range of applications. An example for application in combined heat and power will be given.